PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA BOOKLET TERHADAP PENGETAHUAN IBU DALAM PENCEGAHAN ISPA PADA BALITA DI WILAYAH KERJA PUSKESMAS BAKUNASE KOTA KUPANG - daniel mola kore (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2021)
Acute Respiratory Infections (ARI) is one of the heaviest respiratory diseases that can cause death, sufferers of ARI will suffer greatly when in the humid, cold or too hot weather and is also a major disease of infant death and often ranks first in the number of morbidity in infants. This study aims to determine the effect of health education with booklet media on maternal knowledge in the prevention of ARI in infants in the Bakunase Community Health Center. This type of research used in this study was pre-experimental using a pre-post test design in a group (One-group pre-post test design). The sample in this study amounted to 92 people who were obtained using probability sampling techniques that match the specified inclusion criteria. Data taken using a questionnaire. Based on the results of the research hypothesis test using the Wilcoxon statistical test obtained p value = 0,000 where the data is said to have an effect if p <0.05 so that H1 is accepted, which means there is a significant influence by providing health education about ARI with media booklets on knowledge of respondents in the Region Bakunase Health Center Work. From the results obtained, it is recommended to health workers at the puskesmas to improve the implementation of health education and to conduct regular health education related to ARI in an effort to improve maternal behavior related to knowledge. Keywords: Health Education, Media Booklet, Mother Knowledge, ARI Disease, Toddler